2018
DOI: 10.1021/acs.jpclett.8b02323
|View full text |Cite
|
Sign up to set email alerts
|

Sizable Excitonic Effects Undermining the Photocatalytic Efficiency of β-Cu2V2O7

Abstract: Copper vanadates have been proposed as promising photoanodes for water-splitting photoelectrochemical cells, but their performance has recently been shown to be severely limited. To understand this behavior, we study the electronic structure and the optical properties of β-CuVO both experimentally and computationally. The measured absorption spectrum shows an absorption peak at 1.5 eV followed by the onset of an apparent continuum at 2.26 eV, as generally found for this class of materials. We perform calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…However, the low photocurrent generation from absorption of photons below~2.3 eV in energy has limited the development of these materials. The recent work on strong excitonic features in b-Cu 2 V 2 O 7 by Wiktor et al 31 offers an explanation for this observation. We hypothesize that relatively high alloying concentration of elements without energetically accessible empty d orbitals in some way disrupts the formation of excitons on neighboring Cu 2+ cations, although further exploration hinges upon identification of the crystallographic location of these alloying elements.…”
Section: Structural Characterizationmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the low photocurrent generation from absorption of photons below~2.3 eV in energy has limited the development of these materials. The recent work on strong excitonic features in b-Cu 2 V 2 O 7 by Wiktor et al 31 offers an explanation for this observation. We hypothesize that relatively high alloying concentration of elements without energetically accessible empty d orbitals in some way disrupts the formation of excitons on neighboring Cu 2+ cations, although further exploration hinges upon identification of the crystallographic location of these alloying elements.…”
Section: Structural Characterizationmentioning
confidence: 93%
“…Recently, theoretical assessment of b-Cu 2 V 2 O 7 via calculations including effects of magnetic order, nuclear quantum motion, and thermal vibrations, combined with experimental optical absorption measurements, has indicated the importance of Cu-centered excitons in both the high-visible absorption and the limited photoactivity of b-Cu 2 V 2 O 7 . 31 A subgap optical absorption peak observed for most copper vanadate phases has previously been ascribed to ligand field allowed d-d localized electronic transitions on the Cu 2+ cations. 19 Wiktor et al 31 identify this transition around 1.5 eV as a localized electron-hole exciton on the same Cu 2+ site, and additionally identify a higher-energy excitonic feature at 2.1 eV corresponding to excitation of the electron to the unoccupied d orbitals of a neighboring Cu 2+ cation.…”
Section: Progress and Potentialmentioning
confidence: 95%
See 1 more Smart Citation
“…47 Since the TRMC shows that there is only minor wavelength dependency on the carrier mobility and lifetime in Cu 2 V 2 O 7 , we attribute the sharp increase in the IPCE of Cu 2 V 2 O 7 below 350 nm to a wavelength-dependent photogeneration yield in this material. Indeed, the first electronic transition in Cu 2 V 2 O 7 is a Laporte-forbidden Cu dd transition, 31,35 like in hematite. It has been suggested that such transitions do not significantly contribute to the photocurrent.…”
Section: Photoelectrochemical Propertiesmentioning
confidence: 99%
“…17 The breadth of these materials development strategies far exceeds the breadth of candidate photoanodes for which they have been deployed. The general bias in scientific research towards continued investigation of well-researched materials is both broadly known and recently evaluated as a limitation on creativity and discovery, 18 21 and computational investigation of β-Cu 2 V 2 O 7 22 to elucidate performance-limiting properties. Of these, only the copper vanadates exhibit a photon energy onset of photoactivity near 2 eV, the desired upper-limit described above.…”
Section: Toc Graphicsmentioning
confidence: 99%